PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP NILAI PERUSAHAAN DENGAN RETURN ON ASSETS SEBAGAI VARIABEL MODERASI (Studi Kasus pada Perusahaan Manufaktur Sub Sektor Industri di BEI Tahun 2015 – 2017) - Ummi Kultsum; Untung Sriwidodo; Suprihatmi Sri Wardiningsih (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2020)
The purpose of this study was to analyse the significance of the effect of good corporate governance on firm value with return on assets as a moderating variable in manufacturing companies in the industrial sub sectors in the Indonesian Stock Exchange period 2015 - 2017. The population in this study are all companies manufacturing industrial sub sectors that have been listed or listed on the Indonesian Stock Exchange in a period 2015 - 2017 of 44 companies. The numbers of samples used was 12 companies, with the sampling technique using purposive sampling. Data collection techniques using documentation studies. Data analysis techniques used are classic assumption test, multiple linear regression analysis,t test, f test, coefficient of determination and absolute difference test. The results of study show that good corporate governance has a significant effect on the companies value of manufacturing sub industry companies. Return on assets does not have a significant effects on the companies value of manufacturing industry sub sector. Return on assets moderates the effects of good corporate governance on the companies value of manufacturing in the industrial sub sector.